Are there black holes in carbonate deposystems? - V. P. Wright (Geologica Acta: an international earth science journal, 2004)
The likelihood that extensive dissolution of aragonite (and high magnesian calcite) takes place during very earlyburial, even in relatively shallow tropical settings, has wide implications for interpreting and modelling ancientlimestones. Some low energy environments may constitute net sinks (black holes) for carbonates. If this is thecase attempts to model sediment budgets and develop depth-productivity profiles for carbonate systems requireas yet unavailable quantitative data on the effects of these processes. We query whether the established trends ofdiminishing carbonate productivity with depth could, for some settings such as ramps, be in part an artifact ofselective, offshore dissolution more than simply due to reduced benthic production. Many fossil assemblagesfrom low energy settings may be limited to refractory (residual) skeletal elements, which limits our ability tomake palaeoenvironmental determinations: some important carbonate grain producers such as the green algaemay have been especially prone to early dissolution. The possibility exists that what is now mud-grade carbonatein low energy deposits may not represent original material deposited from suspension but could representtransformed aragonite from in situ production by the skeletal fauna. The selective removal of labile aragonitic(and high Mg calcite) components could produce sediments that appear to have had the composition of coolwater types, and the reduced diagenetic potential of many Palaeozoic and cool water carbonates could be a consequenceof the effects of early aragonite dissolution rather than due to differences in primary (depositional)composition.